1999
DOI: 10.1007/s150100050026
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of 1,422 Haemophilus influenzae Isolates from Respiratory Tract Infections in Spain. Results of a 1-Year (1996-97) Multicenter Surveillance Study

Abstract: A Haemophilus influenzae multicenter antimicrobial susceptibility surveillance was carried out. An overall beta-lactamase production rate of 25.7% was found, with significant differences between hospitals ranging between 7.9 and 47.9%. Presumable intrinsic resistance was found in 4.6% of strains. No differences in susceptibility were observed between beta-lactamase positive and beta-lactamase negative strains for all antibiotics, except for penicillin, amoxicillin and cefaclor. A higher prevalence of resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 3 publications
1
10
1
Order By: Relevance
“…All other antibiotics tested were very active in vitro against isolates of H. influenzae (levofloxacin, cefditoren, cefotaxime, and cefpodoxime) with a few organisms being non-susceptible to amoxicillin/clavulanate, cefuroxime and clarithromycin. The rate of clarithromycin-resistance found in this study is rather low but in one study carried out in Spain, up to 22.6% of H. influenzae isolates were resistant to this antibiotic [3]. Resistance or diminished susceptibility to such drugs has also been previously reported [3,5,6,10].…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…All other antibiotics tested were very active in vitro against isolates of H. influenzae (levofloxacin, cefditoren, cefotaxime, and cefpodoxime) with a few organisms being non-susceptible to amoxicillin/clavulanate, cefuroxime and clarithromycin. The rate of clarithromycin-resistance found in this study is rather low but in one study carried out in Spain, up to 22.6% of H. influenzae isolates were resistant to this antibiotic [3]. Resistance or diminished susceptibility to such drugs has also been previously reported [3,5,6,10].…”
Section: Discussionsupporting
confidence: 39%
“…New antibiotics should also be tested because the resistance problem is reducing treatment options. As increased rates of antibiotic resistant isolates have been described in countries from the south of Europe [1][2][3][4][5][6], we developed the Antibiotic Resistant Isolates in Southern European countries (ARISE) project as a point prevalence study that looked at isolates collected over a relatively narrow period of time. At the same time cefditoren, a new cephem antibiotic [7,8] was studied and this paper shows the results obtained with H. influenzae, H. parainfluenzae and M. catarrhalis.…”
Section: Introductionmentioning
confidence: 99%
“…The patient had previously been treated with moxifloxacin for 5 days. Most general surveillance studies have shown that the rate of resistance to fluoroquinolones in H. influenzae is low (15). However, this resistance rate could be higher among isolates recovered from patients with chronic respiratory infections, as the clinical management of these patients often includes repetitive treatments with oral quinolones (7,17) and quinolone resistance could be induced as a consequence of this strong antibiotic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Although fluoroquinolones remain among the antimicrobial agents that are the most powerful against H. influenzae in vitro and are also highly effective as oral treatments for respiratory tract infections (15), resistance has been recognized (1,7,16,25). The emergence of Streptococcus pneumoniae and H. influenzae isolates with reduced susceptibilities to ciprofloxacin and other quinolones appears to be a growing problem worldwide for clinical and public health.…”
mentioning
confidence: 99%
“…Three multicenter studies (the Susceptibility to the Antimicrobials Used in the Community in Spain [SAUCE] studies) have been carried out to evaluate the antibiotic resistance rates among respiratory pathogens, including H. influenzae (13,23,31). One of the most remarkable findings was the increasing prevalence of isolates belonging to the BLNAR phenotype.…”
mentioning
confidence: 99%